The Effect of Formulation Excipients on the Penetration and Lateral Diffusion of Ibuprofen on and within the Stratum Corneum Following Topical Application to Humans. Issue 3 (13th January 2014) - Gee, Carol M.; Watkinson, Adam C.; Nicolazzo, Joseph A.; Finnin, Barrie C.
<x xml:space="preserve">Abstract</x> Distribution profiles of topically applied drugs can be influenced by the presence of excipients. This study investigated the effect of common topical excipients on the simultaneous lateral diffusion and stratum corneum (SC) penetration of a model compound, ibuprofen (IBU) in humans. IBU solutions with and without propylene glycol (PG), polyethylene glycol 200 (PEG 200), and/or octisalate (OS) were dosed onto the forearm of participants. At various times, 10 "tape‐strippings" were obtained with perforated concentric tapes and analyzed for IBU concentration and SC protein mass. Complimentary in vitro permeation studies assessed the effect of excipients on the percutaneous absorption of IBU across human skin. Following in vivo application, IBU displayed a greater tendency for lateral diffusion when applied with OS, whereas IBU resisted lateral diffusion when dosed with PG and PEG 200. After 24 h, 25.3 ± 8.0% and 55.5 ± 18.6% of IBU was recovered from the SC in vivo with and without excipients, respectively. There was a twofold–to threefold enhancement in IBU flux in vitro when applied with excipients. The lower IBU recovery from the SC when applied with excipients may be attributed to the permeation enhancement effects of these excipients. The ability of IBU to laterally diffuse appears to be dependent on formulation excipients. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:909–919, 2014